Crystal structure of N-(4-oxo-2-sulfanylidene-1,3-thiazolidin-3-yl)-2-(thiophen-3-yl)acetamide - Vu Quoc, Trung (Acta Crystallogr E Crystallogr Commun, 2017)
The title compound, C(9)H(8)N(2)O(2)S(3), crystallizes with two molecules (A and B) in the asymmetric unit. Both have similar conformations (overlay r.m.s. deviation = 0.209 Å) and are linked by an N—H⋯O hydrogen bond. In both molecules, the thiophene rings show orientational disorder, with occupancy factors of 0.6727 (17) and 0.3273 (17) for molecule A, and 0.7916 (19) and 0.2084 (19) for molecule B. The five-membered rings make an angle of 79.7 (2)° in molecule A and an angle of 66.8 (2)° in molecule B. In the crystal, chains of molecules running along the a-axis direction are linked by N—H⋯O hydrogen bonds. The interaction of adjacent chains through N—H⋯O hydrogen bonds leads to two types of ring structures containing four molecules and described by the graph-set motifs R (4) (4)(18) and R (4) (2)(14).